SiOxCyHz-TiO2 Nanocomposite Films Prepared by a Novel PECVD-Sputtering Process - Oliveira, Lucas Pires Gomes [UNESP] (2021)
Recently, there has been growing interest in the incorporation of particles in plasma deposited thin films to creation of multifunctional surfaces. In this work a new hybrid methodology based on the plasma enhanced chemical vapor deposition (PECVD) of hexamethyldisiloxane combined to the reactive sputtering of TiO2 is proposed for the preparation of SiOxCyHz-TiO2 composite films. Specifically, the effect of the proportion of O2 in the plasma environment on the morphology, chemical structure, elemental composition, wettability, thickness and surface roughness, of the films was studied. Agglomerates of TiO2 (16-83 μm) were detected into the organosilicon matrix with the concentration of particulates growing with the percentage of oxygen in the feed. In general, there was elevation in the angle of contact of the surfaces as the oxygen supply increased. Interpretation is proposed in terms of the influence of the oxygen supply on the TiO2 sputtering rate and in the oxidation of plasma species.